Case Report: Primary low-grade dedifferentiated liposarcoma of the urinary bladder with molecular confirmation - Cui, Jian; Peng, Ran; Zhang, Yahan; Lu, Yang; He, Xin; Chen, Min; Zhang, Hongying (Frontiers in Oncology, 2023)
Liposarcomas originating in the urinary bladder are extremely rare. Only six cases of bladder liposarcoma have been reported, and all have been described as myxoid liposarcomas. Notably, none of the patients underwent molecular testing. Here, we report a dedifferentiated liposarcoma (DDL) that occurred in the urinary bladder, primarily in a 69-year-old Chinese woman, with infrequent low-grade dedifferentiation. Computed tomography (CT) revealed an ill-defined solid mass in the anterior bladder wall. The patient underwent a partial bladder resection. Histologically, the tumor cells with mild-to-moderate nuclear atypia were arranged in fascicular and storiform patterns, mimicking a low-grade fibroblastic tumor. In addition, scattered small foci of typical lipoma-like well-differentiated components were identified. Immunohistochemically, the tumor tested positivity for MDM2, CDK4, and p16. Fluorescence in situ hybridization revealed MDM2 gene amplification in the neoplastic cells. Whole-exome sequencing showed that this tumor also harbored CDK4, TSPAN31, and JUN amplification. At the latest follow-up (85 months after surgery), the patient was alive, with no evidence of disease. To the best of our knowledge, this is the first example of a molecularly confirmed primary bladder liposarcoma and the first case of DDL at this site.